Training in the Use of Automatic Incubator for Kampung Chicken Farmers in Liliba District Kupang NTT - Mulyantini S Sekarsari, Ni Gusti Ayu; Suryatni, Ni Putu Febri; Sinlae, Markus; Lole, Ulrikus Romsen (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This activity aimed to address low kampung chicken production in Liliba district, Kupang City, NTT, and farmers' limited knowledge of using hatching machines. The goal was to increase chicken and egg production through training in incubator use to meet the local demand for chicken meat.Method: Training was provided to three groups of farmers, each consisting of five participants, focusing on using egg hatching machines. The farmers were trained and guided until proficient in machine use.Practical Applications: The use of hatching machines increased chicken production by 80%, improving breeding cycles, chick survival rates, and egg quality. This approach made farming more efficient and sustainable.Conclusion: The activity successfully improved farmers' skills in using hatching machines, accelerating kampung chicken production, and enhancing chick quality to meet local demands.